English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I'm confused by this... maybe someone else can get it.

Use seperation of variables to solve the initial value problem


dy/dx = cos(x) * e^(y+sin x)

x = 0 , y = 0

2006-11-12 08:37:09 · 3 answers · asked by Steven Procter 2 in Science & Mathematics Mathematics

So far I have 1/e^y * dy = cos x * e^sin(x) dx

Could I just say 1/e^y is a constant, so C * dy = cos x * e^ sin(x) dx, then integrate, so C = ∫ (cos x * e ^ sin (x)) dx ?

2006-11-12 08:41:41 · update #1

Solve for in terms of y.

2006-11-12 08:47:31 · update #2

3 answers

dy/dx=cosx*e^y*e^sinx
dy/e^y= cosx*e^sinx*dx
e^-ydy= cosx*e^sinx*dx
integrate
e^-y/(-1)=int. cosx*e^sinx*dx
put sinx=t
cosxdx=dt
-e^-y=int.e^tdt
=e^t+c
=e^sinx+c
put x=0,y=0
-1=1+c
c=-2
-e^-y=e^sinx-2

2006-11-12 08:45:25 · answer #1 · answered by Dupinder jeet kaur k 2 · 0 0

You have done all the hard yards:

1/e^y * dy = cos x * e^sin(x) dx
So ∫e^(-y)dy = ∫e^sin(x) .cos(x) dx
ie -e^(-y) = e^sin(x) + c

So e^(-y) = K - e^sin(x)
Taking lns
-y = ln (K - e^sin(x))
ie y = -ln (K - e^sin(x))
= ln (1/(K - e^sin(x))
When x = 0 y = 0
So 0 = ln (1/(K - 1))
1/(K - 1) = 1
K = 2
Thus y = ln (1/(2 - e^sin(x)))
{= -ln (2 - e^sin(x))}

Check dy/dx = - -cos(x) e^sin(x)/(2 - e^sin(x))
= cos(x) e^sin(x)/e^(-y)
= cos(x)*e^(y + sin(x)) ... QED

2006-11-12 17:00:20 · answer #2 · answered by Wal C 6 · 0 0

dy/dx = cos(x) * e^(y+sin x)
dy/dx = cos(x) * e^y*e^(sin x)
(e^-y)dy = (cos(x) * e^(sin x))dx
let u = sin(x), then du = cos(x)dx
∫(e^-y)dy = ∫(e^u)du
-e^-y = e^u = e^sin(x) + C
-1 = 1 + C
C = -2
e^-y = 2 - e^sin(x)
e^y = 1/(2 - e^sin(x))
y = ln[1/(2 - e^sin(x))], -3.907 + 2nπ < x < 0.766 + 2nπ

2006-11-12 17:36:55 · answer #3 · answered by Helmut 7 · 0 0

fedest.com, questions and answers